Memos to the president : a guide through macroeconomics for the busy policymaker - Schultze, Charles L. (Washington, D.C. : Brookings Institution, 1992)
When policymakers are in need of economic advice, professional economists are never far away. Policymakers, journalists, and citizens all rely on experts to explain various economic developments and policy proposals. While it is fortunate that experts are close at hand, those concerned with choosing or evaluating economic policies should themselves have an understanding of how the economy works. Unfortunately, many policymakers and interested citizens currently lack such knowledge; and they need to know at the least the basics of macroeconomics to make informed decisions on their own. In this.
MEMORANDUM 24 Increasing National Saving and Investment: Some Guiding Principles -- MEMORANDUM 25 Raising National Saving and Investment I: The Economic Consequences -- MEMORANDUM 26 Raising National Saving and Investment II: Tax Changes and Their Effects -- MEMORANDUM 27 Education -- MEMORANDUM 28 Technological Advance -- PART 4 SUMMARY -- MEMORANDUM 29 A Summary of These Memos and How They Differ from What Others Might Have Told You -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T
Includes bibliographical references and index.
JSTOR
Keywords: Macroeconomics; United States -- Economic policy; Macroéconomie.; États-Unis -- Politique économique.; POLITICAL SCIENCE / American Government / Executive Branch; Economic policy; Macroeconomics; United States; Makroökonomie; Politikberatung; Wirtschaftspolitik; USA; Economische politiek; Macro-economie.; ECONOMIC POLICY; UNITED STATES; MACROECONOMICS